Efektifitas Metode Tartili dalam Meningkatkan Kemampuan Membaca Al-Qur’an Santri Siraajul Ummah Bekasi - Muri Noer Fitriah; Masykur H Mansyur; Neng Ulya (FONDATIA, 2022)
The Tartili method is a method in which santri or students read the Qur'an directly (without spelling) and include/practice the discussion of Tartil reading according to the rules of Ulumul Tajwid and Ulumul Ghorib, and is one of the most practical methods and practices for studying Al-Tajwid. Qur'an faster to help students read the Qur'an. Qualitative approach is "a research process that produces descriptive data in the form of written or spoken words from people and observable behavior". And a qualitative approach is an "approach that describes the reality of an event in detail, depth, and comprehensiveness". In addition, the method used by the qualitative approach is also to match "real phenomena with theories and laws or positive norms that apply by using descriptive methods". The purpose of the Tartili Method is to "introduce the habit of reading the Qur'an directly (without spelling), following the rules of Ulumul Tajwid and Ulumul Gharib" and is a practical way of learning the Qur'an. From observations and interviews conducted at the Siraajul Ummah Islamic Boarding School, it can be concluded that the Tartili method of learning al-Qur'an which was attended by around 70 students requires careful and planned preparation to achieve the goals that have been determined before starting the learning process. The aim here is to educate students who can memorize the Qur'an correctly and accurately, according to the rules of memorization and the science of recitation. And the Tartili method is effective in improving the reading ability of Siraajul Ummah students based on its application.